2004
DOI: 10.1016/j.jtcvs.2003.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled prostacyclin is safe, effective, and affordable in patients with pulmonary hypertension, right heart dysfunction, and refractory hypoxemia after cardiothoracic surgery

Abstract: Inhaled prostacyclin seems to be a safe and effective pulmonary vasodilator for cardiothoracic surgical patients with pulmonary hypertension, refractory hypoxemia, or right heart dysfunction. Overall, inhaled prostacyclin significantly decreases mean pulmonary artery pressures without altering the mean arterial pressure. Compared with nitric oxide, there is no special equipment required for administration or toxicity monitoring, and the cost savings are substantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(71 citation statements)
references
References 31 publications
2
67
0
1
Order By: Relevance
“…Advances in the treatment of PH such as prostacyclin, intravenous milrinone, inhaled nitric oxide, sildenafil, and other modalities have ameliorated some of the physiologic consequences of PH 12-14. Almost half of patients undergoing surgery for aortic stenosis have PH (in both this and other studies), 4, 6, 9 and therefore continued efforts to improve the treatment of these patients is warranted.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Advances in the treatment of PH such as prostacyclin, intravenous milrinone, inhaled nitric oxide, sildenafil, and other modalities have ameliorated some of the physiologic consequences of PH 12-14. Almost half of patients undergoing surgery for aortic stenosis have PH (in both this and other studies), 4, 6, 9 and therefore continued efforts to improve the treatment of these patients is warranted.…”
Section: Discussionmentioning
confidence: 74%
“…The EuroSCORE uses only the presence of severe PH (PAP > 60 mm Hg) and the STS risk calculator does not consider PH at all. 10-12…”
Section: Discussionmentioning
confidence: 99%
“…[373839] In a retrospective study of 33 adult ICU patients with hypoxemia and PH from cardiac and noncardiac causes, inhaled prostacyclin improved mPAP and hypoxemia. [40] Other studies and case reports have demonstrated the utility of inhaled prostacyclin and of the prostacyclin analog, iloprost, in reducing PAP and improving cardiac output,[414243] although prospective studies in critically ill patients with PH are lacking.…”
Section: Pharmacologic Therapy Of Pulmonary Hypertensionmentioning
confidence: 99%
“…iNO reduces PAPs and pulmonary vascular resistance, while it does not produce systemic vasodilation, since it is rapidly inactivated by hemoglobin binding. [67103104105106107] PH-specific therapies, used in the perioperative period, include oral or IV sildenafil,[13108109] IV or inhaled epoprostenol,[110111112113114115] inhaled iloprost,[116117118] and IV treprostinil. [119] Endothelin receptor antagonists have a limited role in the acute setting as they are considered long-term therapies for PH.…”
Section: Managementmentioning
confidence: 99%